Electrochemical detection of biomolecules at liquid-liquid interfaces - O’Sullivan, Shane (Curtin University, 2014)
This thesis is concerned with the electrochemistry of proteins at liquid-liquid interfaces. Understanding the behaviour of proteins at the liquid-liquid interface is of fundamental importance to the development of liquid-liquid electrochemistry as a viable method for bioanalysis. This thesis explores new avenues of fundamental protein behaviour, including protein surfactant interactions, selective detection of proteins and protein accumulation at the liquid-liquid interface.